Narrativas sobre lesbianidades sob uma perspectiva interseccional: um estudo com jovens lésbicas das periferias de Fortaleza-CE - Gonzaga, Jamyle Maria de Sousa (2024)
Lesbian experiences have historically been made invisible, both in everyday life and in relation to scientific productions. This invisibilization is intensified as other social markers intersect, with black and peripheral lesbians being the most affected, including by lesbophobia. In 2022, the first stage of the 1st National LesboCenso was launched, which presented results on self-identification, work, health, family, networks and violence. Regarding the last axis, 78.61% of the census participants stated that they had already suffered lesbophobia. Furthermore, according to the Dossier on Lesbocide in Brazil: from 2014 to 2017, there was an increasing rate of this violence in Brazil between those years, with lesbians between 19 and 29 years of age (74%), northeasterners (26%) and non-feminized (55%) were the most affected. Given this, this investigation intends to produce analyzes guided by the following problem question: What narratives about lesbian experiences are produced by young lesbians living on the outskirts of Fortaleza? As a general objective, the research proposed to analyze, from an intersectional perspective, the lesbian experiences of young lesbians living on the outskirts of Fortaleza, based on their narratives about their life trajectories. This objective unfolds into the following specific objectives: to understand how markers of gender, sexuality, race and class intersect in the life trajectories of young lesbians living in the outskirts of Fortaleza; problematize how lesbophobia is expressed in the trajectories of young lesbians living in peripheral areas and their intersections with racial and class oppression; and identify which practices of re-existence in the face of lesbophobia have been produced by young lesbians from the outskirts of Fortaleza. To this end, the methodological design of the research assumed a qualitative perspective, combined with subaltern feminist perspectives, which articulate gender with other social markers. The feminist epistemology used in this research is black lesbofeminist, which is de(s)colonial and uses intersectionality as a method, proposing to think about the singularities of lesbian existences, starting, above all, from women, black and non-heterosexual. Autobiographical narrative interviews were carried out with 4 young lesbians living on the outskirts of Fortaleza. The results point to: compulsory heterosexuality is the common condition in the lesbian experiences of young people from the outskirts of Fortaleza; the social markers of gender, sexuality, race and class act inseparably, producing different lesbian experiences as they intersect; dyke is the materiality of the intersection of gender, sexuality, race and class; and race is the backbone of the intersection of gender, sexuality, race, and class. It was evidenced that lesbian experiences are crossed by different forms of lesbophobia, discussing family lesbophobia, lesbophobia and religious fundamentalism, corrective sexual violence as a form of lesbophobia, lesbophobia in the job market, lesbophobia in the territory and lesbophobia committed by strangers, denoting that there are no safe spaces for lesbians, with this violence intensifying as social markers and devices intersect. Finally, the resistance and re-existence established by the participants in the face of lesbophobia are highlighted.